2008
DOI: 10.1021/bi801977j
|View full text |Cite
|
Sign up to set email alerts
|

Competition between Reversible Aggregation and Loop Formation in Denatured Iso-1-cytochrome c

Abstract: The competition between intramolecular histidine-heme loop formation and ligand-mediated oligomer formation in the denatured state is investigated for two yeast iso-1-cytochrome c variants, AcH26I52 and AcA25H26I52. Besides the native His 18 heme ligand, both variants contain a single His at position 26. The AcA25H26I52 variant has Pro 25 mutated to Ala. The concentration dependence of the apparent pKa for His 26-heme binding in 3 M gdnHCl indicates that the P25A mutation disfavors oligomerization mediated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Such bimolecular step is very fast, indicating that intermolecular contacts between denatured proteins occur rapidly even in dilute solution. Such intermolecular contacts have been seen by Tzul et al…”
Section: Resultsmentioning
confidence: 99%
“…Such bimolecular step is very fast, indicating that intermolecular contacts between denatured proteins occur rapidly even in dilute solution. Such intermolecular contacts have been seen by Tzul et al…”
Section: Resultsmentioning
confidence: 99%
“…57 Equilibrium studies of Gdn ion-unfolded yeast iso-1-cyt c showed that intermolecular His26−heme dimers occur in 3 M GdnHCl at pH <5.0 at relatively low protein concentrations. 58 The amount of cyt c oligomers obtained by folding with the desalting method decreased by more than 50% when the pH was decreased from 7.0 to 4.0 (Figure S5 of the Supporting Information), where the amount of bis-His-coordinated species of the unfolded state decreases. 37 These results show that certain amount of domain-swapped dimers may be formed from the bis-His-coordinated species in the unfolded state.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The unfolded state of cyt c is reported to make a contribution to the stability of the protein . Equilibrium studies of Gdn ion-unfolded yeast iso-1-cyt c showed that intermolecular His26–heme dimers occur in 3 M GdnHCl at pH <5.0 at relatively low protein concentrations . The amount of cyt c oligomers obtained by folding with the desalting method decreased by more than 50% when the pH was decreased from 7.0 to 4.0 (Figure S5 of the Supporting Information), where the amount of bis-His-coordinated species of the unfolded state decreases .…”
Section: Discussionmentioning
confidence: 99%
“…Progress in protein folding has been closely linked with technical advances in spectroscopy and fast kinetics. T-jump and other laser-initiated techniques have provided rich kinetic information on the formation of α-helices and β-hairpins, which spans the high nanosecond to low microsecond time range, as well as the folding of some small proteins and domains. Advances in rapid mixing and detection methods prompted a renaissance of continuous-flow techniques. , By coupling an efficient capillary ball mixer with a sensitive charge-coupled device (CCD) camera, we can routinely monitor fluorescence or absorbance changes with a dead time as short as 40 μs, which has yielded a wealth of information on early stages of protein folding. , …”
Section: Introductionmentioning
confidence: 99%